Role of Inositol Poly-Phosphatases and Their Targets in T Cell Biology - Srivastava, Neetu; Sudan, Raki; Kerr, William G. (Frontiers in Immunology, 2013)
T lymphocytes play a critical role in host defense in all anatomical sites including mucosal surfaces. This not only includes the effector arm of the immune system, but also regulation of immune responses in order to prevent autoimmunity. Genetic targeting of PI3K isoforms suggests that generation of PI(3,4,5)P3 by PI3K plays a critical role in promoting effector T cell responses. Consequently, the 5’- and 3’-inositol poly-phosphatases SHIP1, SHIP2 and PTEN capable of targeting PI(3,4,5)P3 are potential genetic determinants of T cell effector functions in vivo. In addition, the 5’-inositol poly phosphatases SHIP1 and 2 can shunt PI(3,4,5)P3 to the rare but potent signaling phosphoinositide species PI(3,4)P2 and thus these SHIP1/2, and the INPP4A/B enzymes that deplete PI(3,4)P2 may have precise roles in T cell biology to amplify or inhibit effectors of PI3K signaling that are selectively recruited to and activated by PI(3,4)P2. Here we summarize recent genetic and chemical evidence that indicates the inositol poly-phosphatases have important roles in both the effector and regulatory functions of the T cell compartment. In addition, we will discuss future genetic studies that might be undertaken to further elaborate the role of these enzymes in T cell biology as well as potential pharmaceutical manipulation of these enzymes for therapeutic purposes in disease settings where T cell function is a key in vivo target.